STUDYING SOCIAL CAPITAL IN HOUSING NEIGHBORHOODS- DOES TENURE MATTER? - Inga Britt Werner; Kerstin Klingborg (European Regional Science Association (ERSA), 2010)
As generally in Sweden, the municipality of Stockholm owns a major proportion of the rental housing stock, through its housing companies. At present tenants are offered to buy the real estate units from the municipal housing companies, in the form of tenant-owners associations. This extensive process of conversion of tenure will have major influence on the Stockholm housing market, also in respects such as the relationships between residents and between residents and the society's institutions. The aim of the study is to analyze whether social capital, here in forms of trust and norms as well as the resulting collective action and conflicts, changes with conversing tenure. The design of the study is quasi experimental. Ten buildings in five neighborhoods are chosen pair wise; one already converted into tenant-owners associations and one assumed to continue being owned by the municipal housing company. Data are collected through telephone interviews at two occasions: spring 2008 and spring 2010. Interviews with key persons of the management staff in the five neighborhoods are carried out to compare the two kinds of tenure with design principles of effective institutions (Ostrom 1990). This paper analyzes the results of the first round of interviews: 300 telephone interviews with residents and 15 face to face interviews with management staff. Analysis methods for data from the interviews of residents are cross tabulations with Chi-square and Mann-Whitney tests, factor and regression analyses. Results indicate that residents forming tenant-owners associations have more trust in neighbors in the neighborhood and in politicians at local and municipality levels but less trust in the housing company and the neighborhood police than those continuing to rent. Also indicated are local versions of social capital not only related to the conversion process. Interview results indicate that the studied rental housing institutions differ from the ideal design principles referring to Ostrom. For example, the first of her design principles: clearly defined boundaries, seems to be problematic for the housing companies. Unauthorized subletting and high mobility rates contribute to uncertainty of who has the right to use common resources, leading to conflicts and dwindling norms.
Keywords: 330